Determination of the permeability coefficient and airflow resistivity of nonwoven materials. Issue 1 (January 2022) - Yang, Tao; Hu, Lizhu; Petrů, Michal; Wang, Xiaomeng; Xiong, Xiaoman; Yu, Deyou; Mishra, Rajesh; Militký, Jiří
Air penetration behavior plays a vital role in the performance of fibrous material in various industrial applications. Two parameters, the permeability coefficient and airflow resistivity, can describe the air penetration behavior of fibrous material. FX 3300 Textech Tester III and AFD300 AcoustiFlow devices were used to respectively characterize the permeability coefficient and airflow resistivity of nonwoven materials. Nonwoven samples were compressed due to the load from the test head of the FX 3300. Finite element analysis along with the mathematical method were implemented to recover the airflow permeability of samples at the uncompressed state. The effects of pressure drop on the airflow velocity and permeability coefficient were analyzed by the Ergun-type model. The determination of airflow resistivity based on the permeability coefficient is carried out via two approaches, that is, the direct method and the extrapolation method. The results show that the airflow velocity is not linearly related to the pressure drop, which differs from Darcy's law. This non-linear relation is mainly attributed to the influence of frictional loss. By comparing the relative error between assessed and measured airflow resistivity, most of the assessed values of the compressed samples are overestimated. The results also suggest that the direct and extrapolation methods are applicable to assess airflow resistivity on an airflow velocity (or air permeability) test device. Moreover, the Ergun-type model is also applicable to determine the permeability coefficient and airflow resistivity of nonwoven materials.